Hand grip strength and associated factors among nurses in Birjand, Iran in 2022: A cross-sectional study - Farzane Vatani Moghaddam; Zeinab Saremi; Mohammad Hamed Hosseini (Nursing and Midwifery Studies, 2025)
Background: Handgrip strength is a critical component of a nurse's ability to perform essential duties, including patient handling and the use of medical instruments. However, there is limited data on the handgrip strength of nurses and the factors influencing it.Objectives: This study aimed to assess handgrip strength and its associated factors among nurses in Birjand in 2022.Methods: In this cross-sectional study, we selected 280 nurses employed at three educational hospitals in Birjand through stratified random sampling. Handgrip strength was measured using a Jamar hydraulic dynamometer. Upper extremity discomfort was evaluated using the Nordic questionnaire. Data analysis was performed with SPSS software (version 19), employing independent samples t-tests, chi-square tests, and Pearson's correlation coefficient. A p-value of less than 0.05 was considered statistically significant.Results: The mean handgrip strength was 48.99 ± 6.40 kgf for males and 21.94 ± 5.74 kgf for females. Notably, 62.4% of female participants and 4.5% of male participants reported experiencing upper extremity discomfort. A significant correlation was found between handgrip strength and variables such as sex, age, work experience, weight, height, routine exercise, and body mass index (P < 0.001). Furthermore, nurses reporting upper extremity discomfort exhibited significantly lower handgrip strength (P < 0.001).Conclusion: Insufficient physical fitness and upper extremity discomfort are associated with reduced handgrip strength among nurses. Therefore, it is recommended that regular exercise, annual clinical evaluations, and appropriate treatment and rehabilitation strategies be implemented to sustain handgrip strength in nursing professionals.